2018
DOI: 10.12659/msm.909378
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TBX3 in Hepatocellular Carcinoma and Its Clinical Implication

Abstract: BackgroundHepatocellular carcinoma (HCC) is the fifth most common malignancy in China, and China’s annual number of new cases accounts for about 45% of the world total. This research was aimed to study the expression of TBX3 protein in HCC and exploring its clinical significance.Material/MethodsWe collected tumor tissues and adjacent non-tumoral tissues of 174 patients with HCC undergoing surgical resection. The expression of TBX3 protein in different tissues and cell lines in vitro (LO2, HHL-5, MHC97-L, MHC97… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Furthermore, TBX3 promotes chondrosarcoma cell proliferation by directly binding to and repressing the p21 WAF1/CIP1 promoter at a T-element at −121 bp (Willmer et al, 2016a(Willmer et al, , 2016b. More recently, TBX3 was shown to promote proliferation of papillary thyroid carcinoma cells through repressing p57 KIP2 (Li et al, 2018a(Li et al, , 2018b. This resulted from TBX3 binding and recruiting the PRC2 and HDACs 1 and 2 to the region of the CDKN1C promoter that regulates p57 KIP2 expression.…”
Section: The Role Of Tbx3 In Promoting Proliferation and Bypassing Senescence Apoptosis And Anoikis-a Fundamental Trait Of Cancer Cells Imentioning
confidence: 99%
“…Furthermore, TBX3 promotes chondrosarcoma cell proliferation by directly binding to and repressing the p21 WAF1/CIP1 promoter at a T-element at −121 bp (Willmer et al, 2016a(Willmer et al, , 2016b. More recently, TBX3 was shown to promote proliferation of papillary thyroid carcinoma cells through repressing p57 KIP2 (Li et al, 2018a(Li et al, , 2018b. This resulted from TBX3 binding and recruiting the PRC2 and HDACs 1 and 2 to the region of the CDKN1C promoter that regulates p57 KIP2 expression.…”
Section: The Role Of Tbx3 In Promoting Proliferation and Bypassing Senescence Apoptosis And Anoikis-a Fundamental Trait Of Cancer Cells Imentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC), a heterogeneous group of diseases, is the sixth most common cancer worldwide, causing about 60 000 deaths per year [ 1 ]. In China, HCC is the fifth most commonly diagnosed cancer after lung cancer, gastric cancer, esophageal cancer, and breast cancer, and it has a high mortality rate [ 2 ]. A series of novel therapeutic strategies are now available for HCC, including surgical resection and liver transplantation, which have become primary surgical treatment strategies for HCC [ 3 ]; however the 5-year survival rate after surgery is still only 15–40% [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that Nrf2 activation declines with age [ 90 , 91 ] and is downregulated in diseases such as type 2 diabetes [ 92 ] and atherosclerosis [ 93 ]. In view of this, it could be speculated that older, diseased individuals are more likely to benefit from an intervention attempting to reestablish Nrf2 activation than young, healthy individuals, in whom Nrf2 activation is unlikely to be impaired.…”
Section: Discussionmentioning
confidence: 99%